(untitled) (American Journal of Islam and Society, 2013)
In this article, we argue analytically that democratic iteration is a plausible discourse to mitigate terrorism in the contemporary world. By far the most pertinent position we advance is the need for democratic iteration among people who perpetrate acts of violence and those subjected to the perpetration of such acts. An education for freedom from terror is justifiable in the sense that such a view of education would cultivate intercultural understanding and uncompromising attitudes toward people’s beliefs and values – that is, the possibility for critical attitudes and social change would be enhanced. The afore-mentioned form of education (in Islam) is emancipatory and would hopefully instill in people the willingness and openness to engage in interculturalism, to appreciate the possibility of changing the world by seeing and thinking about things differently (including terrorism). We contend that terrorism is a form of political violence that has not necessarily been caused by education; rather, it is caused by the uncertainty, hopelessness, and instability that lead to human deprivation, exclusion, dystopia in the world and, ultimately, outrage. Yet we posit that an education in Islam about experiencing the other (as opposed to knowingness) through deliberative iteration would serve as a meaningful mitigation of terror.